Hepatic SREBP signaling requires SPRING to govern systemic lipid metabolism in mice and humans - Hendrix, Sebastian; Kingma, Jenina; Ottenhoff, Roelof; Valiloo, Masoud; Svecla, Monika; Zijlstra, Lobke F.; Sachdev, Vinay; Kovac, Kristina; Levels, Johannes H. M.; Jongejan, Aldo; de Boer, Jan F.; Kuipers, Folkert; et al. (Nature communications, 2023)
The sterol regulatory element binding proteins (SREBPs) are transcription factors that govern cholesterol and fatty acid metabolism. We recently identified SPRING as a post-transcriptional regulator of SREBP activation. Constitutive or inducible global ablation of Spring in mice is not tolerated, and we therefore develop liver-specific Spring knockout mice (LKO). Transcriptomics and proteomics analysis reveal attenuated SREBP signaling in livers and hepatocytes of LKO mice. Total plasma cholesterol is reduced in male and female LKO mice in both the low-density lipoprotein and high-density lipoprotein fractions, while triglycerides are unaffected. Loss of Spring decreases hepatic cholesterol and triglyceride content due to diminished biosynthesis, which coincides with reduced very-low-density lipoprotein secretion. Accordingly, LKO mice are protected from fructose diet-induced hepatosteatosis. In humans, we find common genetic SPRING variants that associate with circulating high-density lipoprotein cholesterol and ApoA1 levels. This study positions SPRING as a core component of hepatic SREBP signaling and systemic lipid metabolism in mice and humans. Hendrix et al show that absence of hepatic Spring dramatically lowers levels of lipids in the liver and plasma in mice, and protects from development of diet-induced steatosis. In line, genetic variation in SPRING is associated with lipid levels in humans.